Experimental, behavioral and information economics on road accidents in Colombia - Gutiérrez Ossa, Jahir Alexander; Mira Olano, Luz Elena (Universidad Francisco de Paula Santander, 2024)
In principle, emphasis will be placed on the experimental foundation of the behavior and information that explains road accidents, followed by the trajectory that the divisions of the economy fulfill for the same purpose, to finally postulate cross-sectional and continuous models, which can give an idea about what the analysis of road accidents in the economy implies for each case, keeping in mind the possibility of proposing roadmaps as to what this entails with respect to decision theory, rational choice and incomplete information that falls on the accident, explaining said situation to a circumstantial fact unrelated to prevention and, which is due to the nature of the episode that can be analyzed in short periods, but that requires greater review when an economic nature is sought. of road accidents, it is considered that it is based on experimental economics, behavior and information from which facts are explained that threaten, contravene or harm the condition and human decisions in a direct and indirect way towards society. consider the foundation of the economy on accidents in Colombia, surpassing public health. The experimental concept denotes that it does not behave like a market in the strict or exact sense in terms of demand, supply, market prices or general economic equilibrium, and is incomplete, because it is not taken under rational criteria but rather are unexpected situations. Therefore, the article is a reflection, rather than a review or results, since the information is scarce and depends more on the discretion of the actors involved as well as theirs towards the health system according to the nature of the accident. road, therefore, a univocal concept is still not clear, but for the purposes of the article the latter is taken to indicate the experimental.